Qualification and methods of laser capsulotomy in pseudophakic eye - Rusin-Kaczorowska, Katarzyna; Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Posterior capsule opacification (PCO) called secondary cataract is one of the most common late complication after the cataract surgery. This drawback might happened in 25 to 50 per cent in adult group and 51 to 100 per cent in children and adolescent group during 2 to 5 years after surgery. Currently Nd: YAG capsulotomy is the best method of secondary cataract treatment. Decision making about PCO should be based on thorough analysis of potential risk factors and advantages which follows that procedure. Advantages are: improvement of visual acuity, improvement of contrast sensivity, reducing glare and better appearance of eye fundus. However after capsulotomy some complications may happen : cystoid macular edema (CME), retinal detachment (RD), intraocular pressure increase (IOP), intraocular lens (IOL) dislocation .Nowadays it is growing awareness of prevention PCO. Counteracting arise PCO include treatment before, during and after surgery and it is strictly connected with reduction of inflammatory reaction, proper of surgical technique. In our publication we would like to stress some important issue about qualification process and techniques of Nd: YAG capsulotomy.